Between Foreignness and Proximity to European Standards. Poles’ Attitudes to the Division of Roles in the Family versus the Values of the Work-Life Balance Directive - Kubicka, Sara (Sensus Historiae, 2024)
Directive 2019/1158 of the European Parliament and of the Council (EU) of June 20, 2019, also called the work-life balance directive, was implemented into Polish law on April 26, 2023. The directive establishes minimum requirements to guarantee equality for women and men regarding labor market opportunities by facilitating work and family life reconciliation. It includes rights related to paternity leave, parental leave, and childcare leave, as well as flexible work arrangements for employees who are parents or caregivers. In doing so, it creates measures to ensure the effectiveness of these solutions. Polish society’s rather conservative views on the division of roles in the family, as presented by opinion polls, are reflected in statistics on the gender burden of household duties. The work-life balance directive aims to increase the involvement of European fathers in caring for children and loved ones in need. As a result of the directive’s implementation, fathers, previously reluctant to exercise their parental rights, have been given opportunities that will allow them to become more involved in family life. If the directive encouraged men to exercise their entitlements, it would be a significant step toward enabling women to become active in the workforce and return to the labor market more quickly after the birth of a child. At the same time, the time a father could spend at home positively impacts family relations and bonding with his child.